2019
DOI: 10.1016/j.cmi.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and microbiological features of bacteraemia with Gram-positive anaerobic cocci: a population-based retrospective study

Abstract: GPAC bacteraemia is much more common than previously reported. GPAC-bacteraemia is a condition with significant mortality mainly affecting elderly persons with comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
37
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 34 publications
9
37
0
1
Order By: Relevance
“…However, since combined data of clinical characteristics about P. micra and other Parvimonas spp. were demonstrated in that study, we described the results of the literature by Badri et al in the section of discussion [9]. In 27 literature cases, P. micra bacteremia was frequently associated with spondylodiscitis (8/27, 29.6%), oropharyngeal infection (7/27, 25.9%) intraabdominal abscess (4/27, 14.8%), GIT infection (3/27, 11.1%), IE (3/ 27, 11.1%), and septic pulmonary emboli (3/27, 11.1%).…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…However, since combined data of clinical characteristics about P. micra and other Parvimonas spp. were demonstrated in that study, we described the results of the literature by Badri et al in the section of discussion [9]. In 27 literature cases, P. micra bacteremia was frequently associated with spondylodiscitis (8/27, 29.6%), oropharyngeal infection (7/27, 25.9%) intraabdominal abscess (4/27, 14.8%), GIT infection (3/27, 11.1%), IE (3/ 27, 11.1%), and septic pulmonary emboli (3/27, 11.1%).…”
Section: Resultssupporting
confidence: 57%
“…1) and were mostly detected using MALDI-TOF MS or 16S rRNA gene sequencing ( Table 2 and sTable 1). In a recent population-based study, GPAC bacteremia, identified using MALDI-TOF MS or 16S rRNA gene sequencing, was reported to be much more common than previously reported with an annual incidence of 3.4 cases per 100,000 persons per year [9], while P. micra was the most commonly isolated in the study. Thus, these new techniques might enable accurate diagnosis of P. micra bacteremia for appropriate treatment.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…This bacteria is implicated in a range of infections including urinary tract infections, necrotizing pneumonia, Necrosis and acute inflammation extend to involve the perinephric adipose tissue (10× magnification). Blue ink was placed at the time of grossing to denote the surface of the specimen infective endocarditis, and meningitis [9]. Finegoldia magna, and other anaerobic bacteria, are well known as gas-producing pathogens.…”
Section: Discussionmentioning
confidence: 99%